2017
DOI: 10.1108/md-08-2016-0607
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the curvilinear relationship between workplace ostracism and knowledge hoarding

Abstract: Purpose The purpose of this paper is to explore the curvilinear relationship between workplace ostracism (supervisor ostracism and co-worker ostracism) and knowledge hoarding by using the conservation of resources theory. In addition, the paper predicts one possible situational context (political skill) that may influence employees’ reaction to ostracism. Design/methodology/approach Using a two-wave research design, the authors collected data from 240 samples in a Chinese diversified company. Hierarchical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
117
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(123 citation statements)
references
References 63 publications
6
117
0
Order By: Relevance
“…First, previous studies on the antecedents of knowledge hiding have confirmed that an interpersonal antecedent is a critical factor in predicting knowledge hiding (Connelly et al, ). However, most of the literature focuses on the relationships among coworkers and neglects the quality of supervisor–subordinate relationship (Connelly et al, ; Zhao et al, ; Zhao & Xia, ). As Tepper et al () noted, the relationship between an employee and his or her immediate supervisor is the most important one among the interpersonal relationships developed at work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, previous studies on the antecedents of knowledge hiding have confirmed that an interpersonal antecedent is a critical factor in predicting knowledge hiding (Connelly et al, ). However, most of the literature focuses on the relationships among coworkers and neglects the quality of supervisor–subordinate relationship (Connelly et al, ; Zhao et al, ; Zhao & Xia, ). As Tepper et al () noted, the relationship between an employee and his or her immediate supervisor is the most important one among the interpersonal relationships developed at work.…”
Section: Discussionmentioning
confidence: 99%
“…We included employees' gender, age, and job tenure as control variables because these variables have potential influences on employees' knowledge hiding behaviors (e.g., Bogilović, Černe, & Škerlavaj, 2017;Peng, 2013;Zhao & Xia, 2017). Specifically, gender was coded as a dummy variable (1 = male, 0 = female), and age and job tenure were measured in years.…”
Section: Control Variables (Time 1)mentioning
confidence: 99%
See 1 more Smart Citation
“…Zhao et al. ; Zhao and Xia ). However, it is not always the case that all the exchange between the leaders and organisation members can be explained by social exchange theory (e.g.…”
Section: Foci Of Knowledge Hiding Researchmentioning
confidence: 99%
“…However, some scholars recognize knowledge hoarding as intentional 54,55 . On the other hand, knowledge hiding refers to the intentional attempts of withholding or concealing one"s knowledge which has been requested by others 56,57 .…”
Section: Knowledge Withholding Among Academics In Higher Academic Insmentioning
confidence: 99%